PENGARUH METODE, PARALLEL TALK TERHADAP KEMAMPUAN PEMAHAMAN BAHASA RESEPTIF PADA ANAK SPEECH DELAY DI TK ABA AMONG PUTRO II - Putri Yasmin Mumtaz; Yulian Agus Suminar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Putri Yasmin Mumtaz, 21144500034. An Analysis of the Parallel Talk Method's Effect on Receptive Language Understanding in Speech-Delayed Students at TK ABA Among Putro II. Students with speech delay at TK ABA Among Putro II Kasihan experience difficulties in their receptive language abilities. This study aims to determine the effect of the parallel talk method on the receptive language skills of a child with speech delay at TK ABA Among Putro II. The research was conducted in November 2025. This study employed a quantitative approach with an experimental method using the Single Subject Research (SSR) design. The subject of this study was one student with speech delay impairment. Data collection techniques were conducted through observation and frequency measurement of correct responses. The research design used was A-B-A, which includes the baseline phase (A1), intervention phase (B), and baseline phase (A2). Data analysis was performed using visual analysis within conditions and between-conditions analysis based on frequency changes. The results showed that in the baseline phase (A1), the subject obtained scores of 4, 5, and 3 across three sessions. In the intervention phase (B), the subject's scores increased to 7, 9, 8, 11, and 13. In the final baseline phase (A2), the subject maintained scores of 11, 12, and 12. Based on these results, it can be concluded that the use of the parallel talk method has a positive effect on improving the receptive language skills of children with speech delay. Keywords: Parallel Talk Method, Speech Delay, Receptive Language.